Self-Regulated Learning among SMK Students (RETAIN, 2020)
This study aimed to investigate SMK students' SRL in enhancing language learning. Self-Regulated Learning itself is the strategy that empowers understudies to assume responsibility for comprehension of information from the teacher by directing their own particular manner of learning. The method of this study was qualitative with basic interpretative design to measure students’ awareness of the existence of SRL and its benefit. The participants of this study were grade 10th students of SMK Negeri 1 Pungging, Indonesia, which consist of 31 students, who have studied English. The questionnaire was applied to measured two aspects; students’ awareness and the ownership of SRL and kinds of SRL components used by EFL learners, using Likert Scales. In addition, the interview was used to explore the benefits of using SRL. The result showed that all of the participants reported moderate to low levels of SRL use (64.3%), meanwhile, (74.4%) of students were using reflect on what worked as the most component of SRL. Furthermore, based on the interview the students get advantages of applying self-regulated learning during the process of studying. To sum up, this study showed that all students employ SRLs, whether they realize or not.